Research progress of copper in diabetes and diabetic kidney disease: a narrative review - Wu, Zongheng; Li, Sumei (Frontiers in Endocrinology, 2025)
Copper is a trace element necessary for the normal growth and development of the human body and is involved in a wide range of physiological processes. However, copper has a dual role in the body: copper deficiency impairs the function of copper-binding antioxidant enzymes, while copper excess can lead to cell damage and even cell death by promoting oxidative stress. Studies have shown that there is a link between copper levels and diabetes, which has been implicated in glucose metabolism and the progression of diabetic complications through a variety of mechanisms. Diabetic kidney disease (DKD), a serious complication of diabetes mellitus (DM), lacks effective prevention and treatment. As a result, the relationship between copper and DKD is beginning to attract the attention of researchers. However, inconsistencies in the results of studies to date suggest that the mechanisms underlying the relationship between copper and diabetes may be more complex. This review summarizes the relevant research progress on the relationship between copper and DM and DKD, with the aim of providing new perspectives and references for research in related fields.